Sosialisasi dan Pencegahan COVID-19 - Sarah Yunara (PROCEEDING UMSURABAYA, 2020)
ABSTRACTThe incidence of COVID-19 cases since the beginning of appearing in December 2019 untilnow has increased sharply until it has spread throughout the world and resulted in a globalpandemic. Deaths caused by the SARS-CoV2 virus were also reported worldwide. The highrisk of transmission causes the government to take various steps to take preventive measures.Individual knowledge and awareness are needed as part of society to prevent transmission ofthis COVID-19 infectious disease.Keywords: COVID-19, SARS-CoV-2, prevention, hand hygiene, mask